From Maimonides to Microsoft : the Jewish law of copyright since the birth of print - Netanel, Neil; Nimmer, David (New York, NY : Oxford University Press, 2016)
In 'From Maimonides to Microsoft', Professors Netanel and Nimmer trace the development of Jewish copyright law by relaying the stories of five dramatic disputes, running from the sixteenth century to the present. They describe each dispute in its historical context and examine the rabbinic rulings that sought to resolve it. Remarkably, these disputes address some of the same issues that animate copyright jurisprudence today: Is copyright a property right or a limited regulatory prerogative? What is copyright's rationale? What is its scope? How can copyright be enforced against an infringer who is beyond the applicable legal authority's reach?
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 28, 2016).
Keywords: Copyright (Jewish law) -- History; Law; Laws of specific jurisdictions & specific areas of law